Analisis Pengendalian Internal Atas Persediaan Obat Pada Apotek Star Medika Abianbase - Ni Kadek Oktaviani; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2023)
This observation was made for to answer situation an implementation internal control system for existing drug supplies at Star Medika Abianbase Pharmacy as seen from internal control standards according to COSO (Committee of Sponsoring Organization). Later the results of the observations can be used by the pharmacy to assess how the internal control system is in the pharmacy. This research is categorized as a qualitative research in which the data is obtained from direct observation of the field, then conducting interviews with several related parties, as well as conducting documentation. from the results of observations it can basically be concluded that Star Medika Abianbase Pharmacy implemented many its internal control COSO (Committee of Sponsoring Organization) supplies. if possible in the future the pharmacy must be able to implement the components of the control environment, control activities, information and communication more optimally because these components have not been implemented optimally